Hierarchy-based salient regions: A region detector based on hierarchies of partitions - Otiniano-Rodríguez K. (2019)
This work received funding from FONDECYT-CONCYTEC (contract number 004-2016-FONDECYT), CAPES (PVE 125000/2014-00), FAPEMIG (PPM 00006-16), and CNPq (Universal 421521/2016-3 and PQ 307062/2016-3).